2020
DOI: 10.1140/epjc/s10052-020-8251-9
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetry with deep learning: particle simulation and reconstruction for collider physics

Abstract: Using detailed simulations of calorimeter showers as training data, we investigate the use of deep learning algorithms for the simulation and reconstruction of single isolated particles produced in high-energy physics collisions. We train neural networks on single-particle shower data at the calorimeter-cell level, and show significant improvements for simulation and reconstruction when using these networks compared to methods which rely on currently-used state-of-the-art algorithms. We define two models: an e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 30 publications
0
90
0
Order By: Relevance
“…Fast precision simulation in particle physics starts with phase space integration [9,10], phase space sampling [11][12][13], and amplitude networks [14,15]. Especially interesting are NN-based event generation [16][17][18][19][20], event subtraction [21], detector simulations [22][23][24][25][26][27][28][29][30], or fast parton showers [31][32][33][34]. Deep generative models can also improve searches for physics beyond the Standard Model [35] or anomaly detection [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Fast precision simulation in particle physics starts with phase space integration [9,10], phase space sampling [11][12][13], and amplitude networks [14,15]. Especially interesting are NN-based event generation [16][17][18][19][20], event subtraction [21], detector simulations [22][23][24][25][26][27][28][29][30], or fast parton showers [31][32][33][34]. Deep generative models can also improve searches for physics beyond the Standard Model [35] or anomaly detection [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The training and the evaluation of the NN models are performed on cells belonging to the topoclusters. Figure 4 shows a comparison between the predicted and truth cell energies for the Graph model for an inclusive energy range of [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] GeV. It illustrates the ability of the ML models to predict the cell fractions over a wide range of energy.…”
Section: Parametric Algorithm Implementationmentioning
confidence: 99%
“…Image-based convolutional NN have been used to study calorimeter shower and also used for hadronic jet tagging, as can be found Refs. [11][12][13][14]. These approaches are based on uniform two or three-dimensional (2D or 3D) images.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of GANs within particle physics are constantly appearing. GANs have been applied in both event generation [37][38][39][40][41][42][43] and detector modelling [44][45][46][47][48][49][50][51][52]. In this section the inference and training speeds of some of these particle physics based GANs are assessed on the IPU hardware and compared to results on the GPU and CPU described in Table 1.…”
Section: Event Generation and Tracking Corrections Using Gansmentioning
confidence: 99%